Dampak Penghentian Operasi PT. Mandala Airlines di Bandara Ahmad Yani Semarang - Idjon Sudjono (Research and Development Agency of The Ministry of Transportation, 2011)
The impact of ceasing temporary operation PT. Mandala Arilines in Achmad Yani Airport at Semarang on January 13th 2011 will effect toward the decreasing air of transport capacity of Semarang—Jakarta routes and Semarang-Banjarmasin routes. In hence, the route Semarang-Banjarmasin flown by Mandala airlines seven times in a week, and route Semarang-Jakarta twelve times per week. By using load factor comparative method, from the result of the research was obtained the increasing of load factor to all routes of airline schedule flow by mandala.